Fishing methods and fishing season of the tropical lobster fisheries of Southern Java, Indonesia - ARIEF SETYANTO; SUMARNO SUMARNO; D. G. R. WIADNYA; CAHYO PRAYOGO; Z. KUSUMA; R. J. WEST; MARTIN TSAMENYI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Setyanto A, Sumarno, Wiadnya DGR, Prayogo C, Kusuma Z, West RJ, Tsamenyi M. 2023. Fishing methods and fishing season of the tropical lobster fisheries of southern Java, Indonesia. Biodiversitas 24: 778-783. Tropical lobster fisheries represent a relatively small-scale but valuable export industry in Indonesia, but in many ways may fall within the category of Illegal, Unreported and Unregulated (IUU) fisheries. The absence of useful fisheries information means the management strategies and plans to manage the fisheries is severely limited. This research aimed to provide information about the fishing gear, methods, and fishing season of the fisheries, as a precursor to the development of fisheries management strategies. The study was conducted at Watukarung, Pacitan (East Java) and Baron, Gunungkidul (Yogyakarta). Fisheries data on lobster catch, fishing methods and fishing effort were collected through direct observation and interviews with fishers, fishery officers and port managers. Catch data were analyzed using ordinations technique to determine the fishing season. Lobsters were captured in various fishing gears throughout the year, but fishers targeting lobsters primarily used specialized lobster nets deployed by small boats and “krendet” (traps) deployed from clifftops as well as from small boat. The main fishing season for lobsters was from November to February each year. Future research needs to investigate fishing capacity and population parameters before any comprehensive fisheries management can be undertaken.